Synthesis of Al-doped zinc oxide nano particle TCO material by simple Sol-Gel method. (July 2020) - Roy, Dhananjoy; Basu, M; Paul, S
Abstract: Transparent Conducting Oxides (TCOs) are thin films of optically transparent and electrically conductive material. They are an important component in a number of electronic devices including liquid-crystal displays, OLEDs, touchscreens and photovoltaics etc. Indium tin oxide (ITO) is the most widely used TCO but its toxic effect and scarcity in nature causes for high cost of the product and hence technology needs a suitable replacement of it. Out of few replaceable materials, Aluminum doped Zinc Oxide (AZO) semiconductive material has been proven its potential replaceability due to its good transparency in the visible light as well as good conductivity. Also Zinc Oxide is abundant in nature and has no toxic effect. Pure ZnO and AZO sample were synthesized by simple low cost sol gel method and characterized optically and electrically. Effects of Al doping into ZnO nano crystal has been studied on transparency and conductivity aspects. It is observed that in both cases there is an optimum Al atoms concentration governed by the defects introduced by interstitial Al atoms in AZO nano crystal.